Total phenolic content, Free radical scavenging and Antimicrobial activities of Passiflora subpeltata seeds - Shanmugam Saravanan and Thangaraj Parimelazhagan (Journal of Applied Pharmaceutical Science, 2013)
The study aimed to investigate the antioxidant and antimicrobial activities of seeds from Passiflora subpeltata. The powdered seed material was subjected to successive solvent extraction in a soxhlet extractor. The antioxidant activities were analyzed the methods of DPPH•, ABTS•+, superoxide radical scavenging and metal chelating activity. The antimicrobial activities of seeds were performed by disc diffusion method. The acetone extract of P. subpeltata seed recorded highest total phenolic (340.70 mg GAE / g extract) and tannin (214.30 mg GAE / g extract) contents and possessed high antioxidant activity. The IC50 value of DPPH was (26.37 μg/mL) and the scavenging activity of superoxide radical was (75.18%). P. subpeltata seeds also demonstrated an effective antibacterial property against seven pathogens and antifungal property against two pathogens tested. Therefore, the results suggest that the seeds of P. subpeltata have promising therapeutic value for natural antioxidant and antimicrobial properties.
Keywords: Passiflora subpeltata, Free radic